2017
DOI: 10.1128/mbio.01412-17
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for EarP-Mediated Arginine Glycosylation of Translation Elongation Factor EF-P

Abstract: Glycosylation is a universal strategy to posttranslationally modify proteins. The recently discovered arginine rhamnosylation activates the polyproline-specific bacterial translation elongation factor EF-P. EF-P is rhamnosylated on arginine 32 by the glycosyltransferase EarP. However, the enzymatic mechanism remains elusive. In the present study, we solved the crystal structure of EarP from Pseudomonas putida. The enzyme is composed of two opposing domains with Rossmann folds, thus constituting a B pattern-typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 106 publications
2
46
0
Order By: Relevance
“…Asp16 of P. aeruginosa EarP corresponds to Asp20 of N. meningitidis EarP, which has been reported as the general base (30). Moreover, replacement of Glu273 of P. putida EarP, corresponding to Glu272 of P. aeruginosa EarP, with a glutamine resulted in undetectable EF-P rhamnosylation in vivo (29). To further analyze the roles of these conserved key residues, we performed site-directed mutagenesis combined with an in vitro assay for EF-P rhamnosylation, detected by mass spectrometry.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Asp16 of P. aeruginosa EarP corresponds to Asp20 of N. meningitidis EarP, which has been reported as the general base (30). Moreover, replacement of Glu273 of P. putida EarP, corresponding to Glu272 of P. aeruginosa EarP, with a glutamine resulted in undetectable EF-P rhamnosylation in vivo (29). To further analyze the roles of these conserved key residues, we performed site-directed mutagenesis combined with an in vitro assay for EF-P rhamnosylation, detected by mass spectrometry.…”
Section: Resultsmentioning
confidence: 92%
“…During the preparation of our manuscript, two independent works on the structure of EarP appeared. R. Krafczyk et al were the first to report the crystal structure of EarP from Pseudomonas putida bound to TDP-Rha (29). These researchers identified that EarP contains two opposing Rossmann fold domains, which classify EarP in glycosyltransferase superfamily B (GT-B).…”
mentioning
confidence: 99%
“…Mutation into an alanine residue, similarly to the mutation of the equivalent residue in NleB1 (E253A), impairs the arginine GlcNAcylation ability of SseK3 and NleB1 without, for the latter, abrogating binding to the target protein ( 22 ). To date, the only available structure of an arginine-glycosylation enzyme is that of the Pseudomonas aeruginosa EarP that catalyzes the transfer of a rhamnose molecule onto the bacterial translation elongation factor EF-P ( 16 ). EarP is an inverting glycosyltransferase belonging to the GT-B family and structurally unrelated to SseK3.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, EarP has three negatively charged residues in the active site (Asp-13, Asp-17, and Glu-273), in close proximity to the sugar, that have been shown to be important in the catalytic activity and play a crucial role in the stabilization of the positive charge of the acceptor guanidino group. Mutation of those residues to alanine, as for the E258A mutation in SseK3, severely impairs EarP enzymatic activity without disrupting substrate binding ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation